Acquisitive prescription as a way of acquiring real estate ownership - Dolović-Bojić Katarina (Anali Pravnog Fakulteta u Beogradu)
The aim of the paper is to determine the exact field of application of the institute of acquisitive prescription, that is, to find the answer in which situations in practice it is possible to fulfill all the conditions required by the legislator and acquire the ownership by usucapio. The main question raised in the paper is whether there is an actual need for the existence of acquisitive prescription in contemporary Serbian law, bearing in mind that the data in the real estate cadastre has been duly kept. The institute of usucapio has also been analyzed from a perspective of application of the reliance principle on land registry. Certainly one of the most problematic question is the justification (and also the legal basis) of this institute having in mind the idea of the inviolability of ownership.